Early term and late preterm birth are associated with poorer school performance at age 5 years: a cohort study. - Quigley, M; Poulsen, G; Boyle, E; Wolke, D; Field, D; Alfirevic, Z; Kurinczuk, J (2012)
OBJECTIVE: To compare school performance at age 5 years in children born at full term (39-41 weeks gestation) with those born at early term (37-38 weeks gestation), late preterm (34-36 weeks gestation), moderately preterm (32-33 weeks gestation) and very preterm (<32 weeks gestation). DESIGN: Population-based cohort (UK Millennium Cohort Study). PARTICIPANTS: Seven thousand six hundred and fifty children born in 2000-2001 and attending school in England in 2006. METHODS: School performance was measured using the foundation stage profile (FSP), a statutory assessment by teachers at the end of the child's first school year. The FSP comprises 13 assessment scales (scored from 1 to 9). Children who achieve an average of 6 points per scale and at least 6 in certain scales are classified as 'reaching a good level of overall achievement'. RESULTS: Fifty-one per cent of full term children had not reached a good level of overall achievement; this proportion increased with prematurity (55% in early term, 59% in late preterm, 63% in moderately preterm and 66% in very preterm children). Compared with full term children, an elevated risk remained after adjustment, even in early term (adjusted RR 1.05, 95% 1.00 to 1.11) and late preterm children (adjusted RR 1.12, 95% CI 1.04 to 1.22). Similar effects were noted for 'not working securely' in mathematical development, physical development and creative development. The effects of late preterm and early term birth were small in comparison with other risk factors. CONCLUSIONS: Late preterm and early term birth are associated with an increased risk of poorer educational achievement at age 5 years.